Epidemiology: Characteristic and risk factors of hemorrhagic stroke: ระบาดวิทยา คุณลักษณะ และปัจจัยทำนายโรคหลอดเลือดสมองแตก - S, Triamvisit; W, Chongruksut; W, Watcharasaksilp; R, Rattanasathien; S, Saisuwan; S, Chaiwang; P, Jaiyen (Biomedical Sciences and Clinical Medicine, 2020)
Object The purpose of this study was to investigate general demographic information concerning hemorrhagic stroke (HS) patients, the prevalence of risk factors, and factors relating to HS in a tertiary hospital in northern Thailand. Methods A retrospective, descriptive study was conducted. The subjects of this study were patients aged 15 years and older, who had been diagnosed with HS and were admitted to Chiang Mai University Hospital from January 2009 to December 2013. Results 3,850 patients of all types of stroke were admitted during the review period. 647 (18.1%) of these patients had suffered HS. 56.9% of the HS patients were male. The average age of the patients was 56.2 years. 77.0% of the patients were transferred to Chiang Mai University (CMU) Hospital from secondary hospitals. 62.3% of HS patients were from Chiang Mai province. 78.8% had universal health care coverage (Golden Card). Of the 647 patients, 62.0% had intracerebral hemorrhage. At admission 62.8% of HS patients had Glasgow Coma Scores (GCS) between 9-15 with the average score being 10.2 (SD=3.9). The top ﬁve risk factors for hemorrhagic stroke were identiﬁ ed as: hypertension, hyperlipidemia, alcohol consumption, smoking, and inconsistent use of prescribed medications. A multivariate analysis indicated the signiﬁcant risk factors were male gender (p<.001, OR=2.9, 95% CI [2.1-4.2], hypertension (p<.001, OR=3.9, 95% CI [2.4-6.2], hypercholesterolemia (p<.05, OR=1.0 [0.9-1.0] and drug non-adherence (p<.05, OR=1.8, 95% CI [1.1-3.4]). Conclusion Most hemorrhagic stroke occurred in male 2.9 times compared with female. The signiﬁ cant risk factors associated with HS were male gender, hypertension, hyperlipidemia, and irregular medication compliance. To lower the incidence HS a number of measures should be taken: public education to emphasize the seriousness and often fatal nature of HS and programs to increase public awareness of HS risk factors.